Global History and Future World Order - Grinin, Leonid; Ilyin, Ilya; Andreev, Alexey (2016)
Abstract: The present article analyzes the world order in the past, present and future as well as the main factors, foundations and ideas underlying the maintaining and change of the international and global order. The first two sections investigate the evolution of the world order starting from the ancient times up to the late twentieth century. The third section analyzes the origin and decline of the world order based on the American hegemony. The authors reveal the contradictions of the current unipolar world and explain in what way globalization has become more profitable for the developing countries but not for the developed ones. The authors also explain the strengthening belief that the US leading status will in-evitably weaken. In this connection we discuss the alternatives of the American strategy and the possibility of the renaissance of the American leadership. The last section presents a factor analysis which allows stating that the world is shifting toward a new balance of power